The Use of Management by Measurements and Management by Results in Syria - N. D. Hurmuz (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
Realizing the necessity to raise the efficiency of state governance resulted in the fact that in the late 20-th century many industrialized and developing countries passed-over to the system of management by results. The article provides the analysis of using principles and basis of management by results and changes in Syria. It is shown that these processes, which started in the early 20-th century, were interrupted by military actions but they resumed now. On the basis of studying current programs and projects of the administrative reform in Syria the author identified problems (military-political conflict, sanctions on the part of the US and EU member-states, isolation of the country) and restrictions (reluctance of civil servants to accept changes, week control over reforms being implemented, the absence of system approach to administrative reforms) of their realization and formulated steps aimed at raising efficiency of Syrian government’s measures and namely: forming a system of responsibility of civil servants on the basis of management by results, strengthening the system of estimation of state programs and projects effectiveness through the central bodies of finance control, designing practical measures of productivity and operative plans, strengthening the trend to using computer technologies and the Internet in the state sector, continuous monitoring of reorganization and restructuring on the micro-level in each state body and restructuring of the state sector each 10-15 years.